Erectile dysfunction and exposure to ambient air pollution in a nationally representative cohort of older men. - Tallon, Lindsay A.; Manjourides, Justin.; Pun, Vivian C.; Mittleman, Murray A.; Kioumourtzoglou, Marianthi-Anna.; Coull, Brent.; Suh, Helen. (2017)
Background: Little is known about the association between air pollution and erectile dysfunction (ED), a disorder occurring in 64% of men over the age of 70, and to date, no studies have been published. To address this significant knowledge gap, we explored the relationship between ED and air pollution in a group of older men who were part of the National Social Life, Health, and Aging Project (NSHAP), a nationally representative cohort study of older Americans.; Keywords: Men, Vasculature, Erectile dysfunction, PM2.5.; Springer Open.